Gentamicin Combined With Hypoionic Shock Rapidly Eradicates Aquaculture Bacteria in vitro and in vivo - Gao, Yuanyuan; Chen, Zhongyu; Yao, Wei; Li, Daliang; Fu, Xinmiao (Frontiers in Microbiology, 2021)
Bacterial pathogens are a major cause of infectious diseases in aquatic animals. The abuse of antibiotics in the aquatic industry has led to the proliferation of antibiotic resistance. It is therefore essential to develop more effective and safer strategies to increase the efficacy and extend the life span of the antibiotics used in aquaculture. In this study, we show that six aquaculture bacterial pathogens (i.e., Aeromonas hydrophila, Vibrio alginolyticus, Edwardsiella tarda, Streptococcus iniae, Vibrio harveyi, and Vibrio fluvialis) in the stationary phase can be rapidly killed after immersion in gentamicin- or neomycin-containing, ion-free solutions for a few minutes. Such hypoionic shock treatment enhances the bacterial uptake of gentamicin in an ATP-dependent manner. Importantly, we demonstrate, as a proof of concept, that gentamicin under hypoionic shock conditions can effectively kill A. hydrophila in vivo in a skin infection model of zebrafish (Danio rerio), completely curing the infected fish. Given that pathogenic bacteria generally adhere to the skin surface and gills of aquatic animals, our strategy is of potential significance for bacterial infection control, especially for small-scale economic fish farming and ornamental fish farming. Further, the combined treatment can be completed within 5 min with a relatively small volume of solution, thus minimizing the amount of residual antibiotics in both animals and the environment.